Production and input-use efficiency in the harvesting activities of medicinal plants in peninsular Malaysia / Mohd Azmi, M.I … [et al.] - M.I, Mohd Azmi; H.O, Mohd Shahwahid; A.G, Awang Noor; M, Rusli (Universiti Teknologi MARA Cawangan Pahang, 2005)
The increasing awareness on herbal remedies and the demand of herbal products leads to rising requirements for local raw medicinal resources by the traditional medicine industries. Although the dependence of the industries on the amount of local medicinal plants required for the production of herbal products is still low when compared to imports, some local medicinal plants are known to be used as the main ingredients in the herbal products processing by Malay traditional medicine manufacturers. Using data from a survey on 33 medicinal plant collectors in Peninsular Malaysia, a descriptive profile of collectors of medicinal plant resources was obtained to provide an overview of the socio-economics of the industry in terms of demographic characteristics of collectors, frequency, duration and travel distance of collecting trips, cost and revenue structure, and production inputs and output. An estimation of a Cobb-Douglas production function was done to determine the relationship between major inputs and medicinal plant production. Both labour and capital inputs in harvesting activities are statistically significant in affecting the amount of medicinal plants harvested. In terms of factor input utilisation, labour input is found to be excessively used when compared to capital input. Both inputs provide positive value marginal products but only for capital was the value marginal product in excess of the cost of its acquisition suggesting that efficiency could be gained by raising capital input utilisations. In the case of labour input, it Jurnal Gading is more efficient for collecting activities to downsize its labour force.